EFEKTIVITAS JEJARING KEMITRAAN KOMUNITAS 1000 GURU BENGKULU DENGAN DONATUR DALAM PELAKSANAAN PROGRAM EDUKASI TRAVELING AND TEACHING - Sibarani, Diana Pebriyanti Rotua Pangurupi; Sofino, Sofino; Hutahuruk , Lenni Mantili (IKIP Siliwangi, 2025)
This study aims to describe the implementation of the partnership network between the Bengkulu 1000 Teachers Community and donors, analyze the effectiveness of the partnership in supporting the Traveling and Teaching program, and identify factors that influence its success. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the partnership pattern is participatory, based on the principle of equality, and implemented transparently. The effectiveness of the partnership is reflected in the program's success in reaching 3T areas, the active involvement of volunteers and donors, and the building of trust between parties. Factors supporting success include intensive communication, shared vision and goals, and flexibility in the roles of each partner. This study confirms that strategic collaboration between communities and donors has an important contribution in strengthening community-based non-formal education practices, while also serving as a model for program sustainability in remote areas.